The multidrug resistance proteins Pgp, MRP, and BCRP as markers for lowering the efficacy of tamoxifen in the treatment of breast cancer - T. A. Bogush; E. A. Dudko; E. A. Bogush; B. E. Polotsky; S. A. Tyulyandin; M. I. Davydov (Опухоли женской репродуктивной системы)
The antiestrogen tamoxifen was examined for its effect on the interaction of monoclonal antibodies with the multidrug resistance markers: with Pgp and MRP1 in the cultured T-lymphoblast leukemia cell line Jurkat and with BCRP in the cultured cervical cancer cell line HeLa. The investigation used immunofluorescence and flow cytofluorimetric assays, primary monoclonal and isotypic antibodies labeled with the fluorescent dyes FITS and PE. After tamoxifen use, there was an increase in specific fluorescence and the number of specifically fluorescent cells on incubation with Pgp and BCRP antibodies and a reduction in those on incubation with MRP1 antibodies. This directly indicates that tomoxifen binds to Pgp, BCRP, and MRP1, which inevitably results in a decrease in the intracellular concentration of the antiestrogen available for the interaction with other cellular targets, including that with estrogen receptors. The authors consider that there is every reason to consider Pgp, BCRP, and MRP1 as markers for lowering the efficacy of tamoxifen in the treatment of breast cancer with the positive estrogen receptor status.